Principals and School Effectiveness, a Fundamental Relation - Oscar Maureira (Universidad Autónoma de Madrid, 2018)
The next work will try to be an contribution to reflection about relation between Management and effectiveness School, emphasize the leadership pedagogy as preponderant role and as a growing priority function and tendency of the School Management's perform, aiming to effectiveness' Schools in its formative work.  So, at different characterizations about studies effectiveness' Schools, describe it the fundamental reference to the factor Management, précising the most high frequency demonstration that it has been recognized. The other hand, to point it some common characteristic that it take off of an Iberian context in attention to Management School and mean characteristics through the Headmaster' role.